Implementation of qualitative and mixed methods researches - Pinto-Llorente, Ana M. (2019)
The objective of the qualitative and quantitative integration in research designs is the reconciliation between paradigms and methods in research in social science. The objective to specify the general epistemological formulations on which qualitative methods are based in more precise and current methodological proposals, since we are in an exciting moment in the qualitative research in which it is appreciated a clear tendency in the use of a mixed methods research. During the Twentieth-First Century that have favoured the rise of mixed methods researches that enhance the mutual invigoration of the two types of methods, and facilitate the triangulation through operations. The aim of this track is to provide a space for reflection and put into practice the foundation, operationalization, and fields of application of qualitative and mixed methods researches.